The Gateway to Computer Science Excellence
+1 vote
60 views
Express the following function in the sum of minterms and The product of the maxterms.

(a) F(A,B,C,D) = B’D + A’D + BD

(b)F(x,y,z)=(xy + z)(xz + y)
in Digital Logic by Boss (10.5k points) | 60 views

2 Answers

+2 votes

we can do this using k-map

by Boss (35.6k points)
0 votes

$a)F(A,B,C,D)=\overline{B}D+\overline{A}D+BD$

$b)F(x,y,z)=(xy+z)\cdot(xz+y)$

 

 

by Veteran (54.7k points)
edited by
0
(b)F(x,y,z)=(xy + z)(xz + y)

(xy + z)=1,3,5,6,7

(xz + y)=0,1,4,5,6,7

now how can you write f=0,1,3,4,5,6,7???

i think you are doing union ,
0
Actually, I did, mistakes, now it is corrected.

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,648 questions
56,459 answers
195,335 comments
100,186 users